2023
DOI: 10.3390/ijerph20085528
|View full text |Cite
|
Sign up to set email alerts
|

Injury Incidence and Its Characteristics in Korean Youth and Collegiate Taekwondo Sparring Athletes: A Retrospective Study

Abstract: This study aimed to identify the incidence of injury and its characteristics in Korean youth and collegiate Taekwondo athletes during 2021 and to provide a suggestion regarding injury incidence. A total of 183 athletes (95 youth and 88 collegiate athletes) who were registered with the Korea Taekwondo Association (KTA) participated. The research was based on the injury questionnaire developed by the International Olympic Committee (IOC). The questionnaire consists of a total of seven items, including four items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although kicks are based on similar techniques and biomechanics, and a high incidence of injuries occurs in the lower extremities, epidemiological data in taekwondo have shown that injuries differ in terms of site and type depending on the subdiscipline [ 12 , 14 ]. In addition, previous studies have reported that navicular drop of the dominant leg, knee hyperextension, and excessive ROM of ankle dorsiflexion and plantarflexion are associated with lower extremity injuries in adolescent taekwondo sparring athletes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although kicks are based on similar techniques and biomechanics, and a high incidence of injuries occurs in the lower extremities, epidemiological data in taekwondo have shown that injuries differ in terms of site and type depending on the subdiscipline [ 12 , 14 ]. In addition, previous studies have reported that navicular drop of the dominant leg, knee hyperextension, and excessive ROM of ankle dorsiflexion and plantarflexion are associated with lower extremity injuries in adolescent taekwondo sparring athletes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in study [21], the Taekwondo skeleton sequences were described by the similarity of the angle trajectories of two and two joint sites, and the identification and classification of Taekwondo behaviors was accomplished through the use of a linear support vector machine. In contrast, study [22] advocated the use of a hierarchical recurrent neural network (HRNN) to segment the Taekwondo skeleton into five pieces, which include the torso, arms, and legs. These parts are then merged with a deep learning approach to simulate the interaction between them.…”
Section: Introductionmentioning
confidence: 99%